Emosi Manusia, Fungsi dan Cara Kerjanya - Kirana, Dewi (TARBIYAH, 2024)
Human emotions apparently have various types and their respective functions. Not only that, these feelings also have various characteristics, groups and their own impacts. Emotions are feelings or affections that arise in a person in response to a certain situation or stimulus. The process of the emergence of emotions involves physiological changes, thoughts, and behaviors that a person can feel. In addition, many factors can trigger the release of a person's emotions. Starting from experience, beliefs, attitudes, interactions and the environment. Human emotions can come out through body language, face, voice or verbal communication.